Inhaled platelet vesicle-decoyed biomimetic nanoparticles attenuate inflammatory lung injury - Jin, Hua; Luo, Renxing; Li, Jianing; Zhao, Hongxia; Ouyang, Suidong; Yao, Yinlian; Chen, Dongyan; Ling, Zijie; Zhu, Weicong; Chen, Meijun; Liao, Xianping; Pi, Jiang; et al. (Frontiers in Pharmacology, 2022)
Acute lung injury (ALI) is an inflammatory response which causes serious damages to alveolar epithelia and vasculature, and it still remains high lethality and mortality with no effective treatment. Based on the inflammatory homing of platelets and cell membrane cloaking nanotechnology, in this study we developed a biomimetic anti-inflammation nanoparticle delivery system for ALI treatment. PM@Cur-RV NPs were designed by combining the poly (lactic-co-glycolic acid) nanoparticles (NPs) coated with platelet membrane vesicles (PM) for the purpose of highly targeting delivery of curcumin (Cur) and resveratrol (RV) to inflammatory lungs. PM@Cur-RV NPs showed good biocompatibility and biosafety both in vitro and in vivo. Accumulation of NPs into lung tract was observed after inhaled NPs. Remarkably, the inhalation of PM@Cur-RV NPs effectively inhibited lung vascular injury evidenced by the decreased lung vascular permeability, and the reduced proinflammatory cytokine burden in an ALI mouse model. The analysis of infiltrated macrophages in the lungs showed that the Cur-RV-modulated macrophage polarized towards M2 phenotype and the decreased histone lactylation might contribute to their anti-inflammation effects. Together, this work highlights the potential of inhalation of biomimetic nanoparticle delivery of curcumin and resveratrol for the treatment of pulmonary diseases.